The ABC of resistance: towards a new analytical framework. Issue 1 (2nd January 2023) - Mikael, Baaz; Lilja, Mona; Schulz, Michael; Vinthagen, Stellan
ABSTRACT: Two significant developments – (1) the rapidly changing world order, and (2) significant gaps in current social science scholarship – call for a further exploration of resistance theories. In this paper, we identify some of the gaps and inconsistencies within the current bulk of research, and seek to contribute to the understanding of resistance, its applications and complexity. In short, this paper discusses three interacting and supporting forms of resistance, including various overlaps and interlinkages between them, which together constitute what we would like to call the ABC of resistance; that is, a voidance resistance, b reaking resistance, and c onstructive resistance.